2017
DOI: 10.3390/su9010095
|View full text |Cite
|
Sign up to set email alerts
|

Quality Perspective on the Dynamic Balance of Cultivated Land in Wenzhou, China

Abstract: Cultivated land in China has faced severe challenges in recent years due to rapid urbanization. In 1997, the "cultivated land requisition-compensation balance" policy was implemented by the government to maintain the quantity and quality of cultivated land. Previous studies mainly focused on the quantity changes of cultivated land. In this study, from a quality perspective, we characterized the occupation and compensation of cultivated land in Wenzhou City utilizing remote sensing and geographic information sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…Due to sterile soil and complex topographic and geographic conditions, the use of cropland is relevant for poverty alleviation and sustainable socioeconomic development [3], which promote the rapid transition of cropland use. Extant related research of cropland use has focused on changes in quantity [4], quality [5], and productivity [6]. In terms of research scale, most studies have concentrated on the macro [7] and middle scale [8].…”
Section: Introductionmentioning
confidence: 99%
“…Due to sterile soil and complex topographic and geographic conditions, the use of cropland is relevant for poverty alleviation and sustainable socioeconomic development [3], which promote the rapid transition of cropland use. Extant related research of cropland use has focused on changes in quantity [4], quality [5], and productivity [6]. In terms of research scale, most studies have concentrated on the macro [7] and middle scale [8].…”
Section: Introductionmentioning
confidence: 99%
“…The cultivated land area was reduced by 12.9%, from its highest amount of 124.88 million hectares in 1991 to 108.49 million hectares in 2007. Having realized the magnitude of cultivated land loss, central government proposed minimum cultivated area requirements in every province [27]. After that, the downward trend eased due to an array of measures designed to protect the cultivated land [28].…”
Section: Land Expropriation Is Unsustainablementioning
confidence: 99%
“…Lu et al reported the spatial patterns of cropland transfer and its implication on ecosystem quality of Jiangsu Province [38]. Lin et al characterized the cropland occupation-compensation from the qualitative and quantitative perspective in Wenzhou from 2005 to 2014 [39].…”
Section: Introductionmentioning
confidence: 99%